2019
DOI: 10.1590/0100-6991e-20192314
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopia e lavado peritoneal no pré-operatório do adenocarcinoma gástrico: podemos modificar a conduta?

Abstract: RESUMO Objetivo: avaliar se a laparoscopia com lavado peritoneal é superior à tomografia computadorizada para o estadiamento do adenocarcinoma gástrico e se pode modificar a conduta cirúrgica do paciente. Métodos: estudo retrospectivo de 46 pacientes portadores de adenocarcinoma gástrico tratados pela equipe de cirurgia digestiva do Hospital de Clínicas de Passo Fundo (RS), de janeiro de 2015 a dezembro de 2018, e submetidos à laparoscopia com lavado peritoneal pré-operatório. Todos os pacientes foram submet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…The main causes of prolonged hospital stay and high hospitalization costs for acute-care hospital patients are related to development of complications, such as an infectious disease 1 . It has also been shown that prolonged hospitalization of general internal medicine inpatients is associated with higher costs and complication rates because of nosocomial infections 2 , and that postoperative complications such as infection increased the cost of hospitalization for patients who underwent a simultaneous pancreas-kidney transplantation 3 . Additionally, a strong relationship among hospitalization costs, healthcare resource utilization, and postoperative complications following a lower anterior resection procedure for rectal cancer has been demonstrated 4 .…”
mentioning
confidence: 99%
“…The main causes of prolonged hospital stay and high hospitalization costs for acute-care hospital patients are related to development of complications, such as an infectious disease 1 . It has also been shown that prolonged hospitalization of general internal medicine inpatients is associated with higher costs and complication rates because of nosocomial infections 2 , and that postoperative complications such as infection increased the cost of hospitalization for patients who underwent a simultaneous pancreas-kidney transplantation 3 . Additionally, a strong relationship among hospitalization costs, healthcare resource utilization, and postoperative complications following a lower anterior resection procedure for rectal cancer has been demonstrated 4 .…”
mentioning
confidence: 99%